INVESTIGATION OF IN VITRO ANTIOXIDANT ACTIVITY AND CYTOTOXICITY ON HUMAN SKIN FIBROBLASTS OF PLUCHEA INDICA (L.) LESS. LEAVES EXTRACT AND DEVELOPMENT TO MICROEMULSION FOR SKIN COSMETIC PRODUCT - K, ITSARASOOK; P, PROMPAMORN; J, TANGHIRANRAT; T, PANICHAKUL (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The aim of this study was to determine the antioxidant activity and cytotoxicity on normal human skin fibroblasts of Pluchea indica (L.) Less. leaves extract and to prepare the extract into microemulsions for application in skin cosmetic ingredient. Methods: The total phenolics and total flavonoids content in ethanolic (30%, 70%, and 95% ethanol) and aqueous extracts of P. indica leaves were determined by Folin-Ciocalteu assay and aluminum chloride method. The quantification of 4,5-O-dicaffeoylquinic acid in the extracts was determined by an ultra-high performance liquid chromatography method. The antioxidant activity of extracts was examined by 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2’-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS), and ferric reducing antioxidant power (FRAP) assays. The cytotoxicity on human fibroblast cell was tested by sulforhodamine B assay. The oil in water microemulsion was prepared by pseudoternary phase diagram. The characterization of prepared-microemulsion including morphology, particle size, and polydispersity index (PDI) was studied and the physicochemical stability of microemulsions was evaluated. Results: All P. indica leaves extracts contain a phenolic, flavonoid, and 4,5-O-dicaffeoylquinic acid contents. The 70% ethanolic extract possessed higher the antioxidant activities than 30% ethanolic, aqueous, and 95% ethanolic extracts, respectively, followed by DPPH, ABTS, and FRAP assay. Thus, the 70% ethanolic extract was selected to develop in skin cosmetic. The 70% ethanolic extract had not cytotoxicity on dermal human skin fibroblasts cell. The microemulsion loaded extract provided a mean particle size of 24.397±1.20 nm with minimum PDI of 0.397±0.05 which shown a spherical shape. The microemulsion loaded extract showed a good stability. Conclusion: From all results, it has concluded that the 70% ethanolic extract of P. indica leaves contain phenolic, flavonoid, and 4,5-O-dicaffeoylquinic acid contents which possessed DPPH, ABTS+, and FRAP activities. In addition, this extract had no cytotoxic to normal human skin fibroblasts. Finally, the microemulsion loaded extract showed a good characterization and physicochemical stability.